EFFECT OF MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE WITH WORK DISCIPLINE AS AN INTERVENING VARIABLE AT BCA KELAPA GADING - Halim, Mario Alexander; Hendratmoko, Hendratmoko (Jurnal Indonesia Sosial Sains, 2025)
This study aims to analyze the effect of motivation and work environment on employee performance with work discipline as an intervening variable at BCA Kelapa Gading. This research was conducted using the PLS-SEM method with the SmartPLS 4.0 program. This study applied a quantitative research design with a survey approach. The number of respondents in this research was 100. The research variables included motivation (X1), work environment (X2), work discipline (Z), and employee performance (Y). The results of this research show that motivation has no significant effect on employee performance, while the work environment has a significant effect on employee performance. Work discipline has a positive and significant effect on employee performance. However, work discipline does not play a mediating role in the relationship between work motivation and employee performance, although it has been proven to be a partial mediating variable in the relationship between work environment and employee performance. This study highlights the practical importance of creating a supportive work environment and enforcing discipline policies to sustain performance improvements in the banking sector. The findings suggest that management should prioritize environmental interventions over motivation-based strategies alone. Future research should expand across multiple branches and incorporate objective performance metrics to validate these findings and explore additional mediating variables that may influence the motivation–performance relationship.